Devenir muxe: torsiones desobedientes de Lukas Avendaño en Réquiem para un alcaraván y en Buscando a Bruno - Guillermina Bevacqua (L'Ordinaire des Amériques)
This article presents an analysis of Lukas Avendaño’s Réquiem para un alcaraván, presented at Centro Cultural Rojas of Universidad de Buenos Aires in 2012. As the play occurred during the last release presentation of El Teje. Primer periódico travesti latinoamericano, the crossings and turnings of a sector of the transvestite/ trans movement in the city of Buenos Aires and the muxe zapoteca community that Avendaño represents. On the other side, on May 10th 2018 his brother Bruño Avendaño was disappeared, joining his name to a long list of Mexican people which are victims of state and non-state violence. As a way to denounce the lack of answers from the legal system and the government, Lukas Avendaño made the performance Buscando a Bruno. In both plays the performer establishes a political gesture through which he turns his autobiographical experience into a collective act, to subscribe to Emilio Santiesteban’s (2008) frequently mentioned phrase that echoes in the Mexican activism of today and its’ art practices: “What place does an art of the body have in a country of disappeared bodies?”